2022
DOI: 10.1002/cne.25342
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific characteristics of cells expressing the cannabinoid 1 receptor in the dorsal horn of the lumbar spinal cord

Abstract: It is becoming increasingly clear that robust sex differences exist in the processing of acute and chronic pain in both rodents and humans. However, the underlying mechanism has not been well characterized. The dorsal horn of the lumbar spinal cord is the fundamental building block of ascending and descending pain pathways. It has been shown that numerous neurotransmitter and neuromodulator systems in the spinal cord, including the endocannabinoid system and its main receptor, the cannabinoid 1 receptor (CB 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…Previous research has mainly focused on CB 1 R functions in cortical regions although functions involving the conserved subcortical regions are currently arousing more interest for a more complete understanding of the endocannabinoid system in conserved behavior and function (Soria‐Gomez et al., 2015). Previous work from our group comparing female mice in estrus and nonestrus (X. Liu et al., 2020) found no statistically significant difference in the number of CB 1 R‐positive cells in most brain regions (X. Liu et al., 2020) and the lumbar spinal cord (Zhang et al., 2022), indicating that the estrous cycle may not contribute to the differences in the number of CB 1 R‐positive cells at different ages. Moreover, two groups in our study, the 4‐ and 86‐week groups, were either sexually immature or aged.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Previous research has mainly focused on CB 1 R functions in cortical regions although functions involving the conserved subcortical regions are currently arousing more interest for a more complete understanding of the endocannabinoid system in conserved behavior and function (Soria‐Gomez et al., 2015). Previous work from our group comparing female mice in estrus and nonestrus (X. Liu et al., 2020) found no statistically significant difference in the number of CB 1 R‐positive cells in most brain regions (X. Liu et al., 2020) and the lumbar spinal cord (Zhang et al., 2022), indicating that the estrous cycle may not contribute to the differences in the number of CB 1 R‐positive cells at different ages. Moreover, two groups in our study, the 4‐ and 86‐week groups, were either sexually immature or aged.…”
Section: Discussionmentioning
confidence: 68%
“…Liu et al, 2020) found no statistically significant difference in the number of CB 1 R-positive cells in most brain regions (X. Liu et al, 2020) and the lumbar spinal cord (Zhang et al, 2022), indicating that the estrous cycle may not contribute to the differences in the number of CB 1 R-positive cells at different ages. Moreover, two groups in our study, the 4-and 86-week groups, were either sexually immature or aged.…”
Section: 5mentioning
confidence: 95%
See 1 more Smart Citation